Proton exchange membrane fuel cell and preparation method thereof
By using a Nafion composite membrane doped with TiO2 and a catalytic layer of a small-particle palladium carbon catalyst in a proton exchange membrane fuel cell, the problem of intimate bonding between the proton exchange membrane is solved, and higher electrochemical activity and stability are achieved.
Patent Information
- Application Number
- CN202411435804.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
AI Technical Summary
In the existing proton exchange membrane fuel cells, the proton exchange membrane is not tightly bound to the electrode, the surface of the catalytic layer is uneven, the electrochemical performance and water absorption and retention properties of the proton exchange membrane are poor, and the specific surface area in the catalytic layer is small, resulting in poor electrical performance.
A Nafion composite film doped with TiO2 is used as a proton exchange film, and a palladium carbon catalyst with a smaller average particle size and crystallinity is combined with a Nafion film material to form a catalytic layer. A carbon black paper is used as a diffusion layer to form a film electrode assembly by hot pressing treatment.
The proton conductivity and chemical stability of the proton exchange membrane are improved, the electrocatalytic performance and mechanical strength of the catalytic layer are enhanced, the electrocatalytic stability is improved, and the electrochemical activity of the proton exchange membrane fuel cell is improved.
Smart Images

Figure CN119518043A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of fuel cells, and in particular, to a proton exchange membrane fuel cell and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cell is a fuel cell that generates electricity and heat by reacting hydrogen-containing fuel with air. It does not require pressurization or decompression, uses polymer proton exchange membrane as the conduction medium, does not contain any chemical liquid, and generates pure water and heat after power generation. Because proton exchange membrane fuel cells use solid electrolyte polymer membrane as electrolyte, they have the characteristics of small size, fast start-up, high energy conversion rate, low temperature start-up, and no electrolyte leakage. In addition, it also has the advantages of fuel diversification, low environmental pollution, low noise, good reliability and maintainability, and has low environmental pollution, almost no nitrogen oxides or sulfur oxides are emitted, and CO 2 Emissions are also more than 40% less than conventional power plants, and are recognized as the most promising power source for aerospace, electric vehicles and regional power stations.
[0003] The proton exchange membrane fuel cells in the prior art have poor electrical performance due to problems such as the lack of tight bonding between the proton exchange membrane and the electrode, the uneven surface of the catalyst layer, the poor electrochemical performance and water absorption and retention performance of the proton exchange membrane, and the small specific surface area of the catalyst layer. Summary of the invention
[0004] The purpose of the present disclosure is to provide a method to solve the problems existing in the prior art, such as the insufficient bonding between the proton exchange membrane and the electrode, the uneven surface of the catalyst layer, the poor electrochemical performance and water absorption and retention performance of the proton exchange membrane, and the small specific surface area in the catalyst layer.
[0005] In order to achieve the above-mentioned object, the present disclosure provides a proton exchange membrane fuel cell in a first aspect, the proton exchange membrane fuel cell comprising a bipolar plate and a membrane electrode assembly arranged in an internal chamber formed by the bipolar plate; the membrane electrode assembly comprises a proton exchange membrane, a catalyst layer and a diffusion layer arranged on both sides of the proton exchange membrane in sequence; the proton exchange membrane is doped with TiO 2 Nafion composite membrane; the catalytic layer includes a palladium-carbon catalyst and a Nafion membrane material; the average particle size of the palladium-carbon catalyst is less than 5 nm and the crystallinity is less than 4%; the diffusion layer is carbon black paper.
[0006] Optionally, the palladium-carbon catalyst has an average particle size of less than 4 nm and a crystallinity of less than 3%.
[0007] Optionally, the carbon black paper comprises carbon black and a polymer binder; the carbon black is acetylene black and / or VXC-72 carbon black; the polymer binder is polytetrafluoroethylene, and the weight ratio of the polymer binder to the carbon black is (0.25~1):1.
[0008] Optionally, the palladium content in the palladium-carbon catalyst is 15-30% by weight.
[0009] Optionally, the bipolar plate is made of stainless steel; a serpentine flow field groove is provided on the inner wall of the bipolar plate, and the ratio of the width of the serpentine flow field groove to the width of the ridge is (0.5~1):1.
[0010] The second aspect of the present disclosure provides a method for preparing the proton exchange membrane fuel cell described in the first aspect, the method comprising: arranging catalyst layers on both sides of the proton exchange membrane, and subjecting the catalyst layers to a first hot pressing process to obtain a first hot pressing component; arranging diffusion layers on the outer sides of the catalyst layers of the first hot pressing component, and subjecting the diffusion layers to a second hot pressing process to obtain a membrane electrode assembly; arranging the membrane electrode assembly in an internal chamber formed by a bipolar plate to obtain a proton exchange membrane fuel cell; the proton exchange membrane is doped with TiO 2 Nafion composite membrane; the catalytic layer includes a palladium-carbon catalyst and a Nafion membrane material; the average particle size of the palladium-carbon catalyst is less than 5 nm and the crystallinity is less than 4%; the diffusion layer is carbon black paper.
[0011] Optionally, the method for preparing the palladium-carbon catalyst comprises: making activated carbon, H 2 PtCl 6 The palladium-carbon slurry obtained by mixing with NaOH solution is vacuum dried to obtain a palladium-carbon dry material; the palladium-carbon dry material and a solid-phase reducing agent are ground to obtain the palladium-carbon catalyst; the solid-phase reducing agent is polyoxymethylene.
[0012] Optionally, the method also includes mixing the palladium-carbon catalyst, Nafion solution and a mixed solvent to form a catalytic slurry; drying the catalytic slurry at a temperature of 120-140° C. to obtain the catalytic layer; the concentration of the Nafion membrane material in the Nafion solution is 1-10% by weight; the mixed solvent is a mixed solution of glycerol and water; the weight ratio of the palladium-carbon catalyst to the Nafion solution is (1-5):1; the weight ratio of the palladium-carbon catalyst, water and glycerol is 1:(1-10):(10-30).
[0013] Optionally, the method for preparing the proton exchange membrane comprises: subjecting a Nafion membrane to sequentially 2 O 2The pretreated Nafion membrane is boiled in a solution and a sulfuric acid solution for 0.5 to 2 hours respectively, and then washed with water to obtain a pretreated Nafion membrane; the pretreated Nafion membrane is immersed in a mixed solution of isopropanol and water to obtain an expanded Nafion membrane; the expanded Nafion membrane is placed in a hydrolysis mixed solution for hydrolysis treatment, and the obtained hydrolyzed Nafion membrane is dried at a temperature of 75 to 85° C. for 18 to 30 hours to obtain the proton exchange membrane.
[0014] Optionally, the H 2 O 2 The mass fraction of the solution is 3-10%; the concentration of the sulfuric acid solution is 0.3-1 mol / dm³; the hydrolysis mixed solution is Ti(OC 4 H 9 ) 4 and isopropanol mixed solution, the hydrolysis mixed solution of Ti(OC 4 H 9 ) 4 The concentration is 0.001~0.005mol / dm³; the temperature of the hydrolysis mixed solution is 60~90℃.
[0015] Through the above technical solution, doped TiO 2 The Nafion composite membrane is used as a proton exchange membrane to form a dense titanium oxide network structure inside the Nafion membrane, which can improve the proton conductivity and chemical stability of the proton exchange membrane while improving the water absorption and water retention performance of the proton exchange membrane. The use of palladium-carbon catalysts and Nafion membrane materials with smaller average particle size and crystallinity can, on the one hand, improve the specific surface area and conductivity of the palladium-carbon catalyst, thereby improving the electrocatalytic performance of the catalyst layer; on the other hand, the Nafion membrane material can act as a binder, which can not only make the catalyst layer have stronger mechanical strength, but also improve the bonding ability between the catalyst layer and the proton exchange membrane, thereby improving the electrocatalytic stability. In addition, the proton exchange membrane fuel cell prepared using the membrane electrode assembly disclosed in the present invention has good electrochemical activity.
[0016] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 It is a schematic diagram of a proton exchange membrane fuel cell disclosed in the present invention.
[0018] Description of Reference Numerals 1 membrane electrode assembly; 2 bipolar plate; 3 anode diffusion layer; 4 cathode diffusion layer; 5 anode catalyst layer; 6 cathode catalyst layer; 7 proton exchange membrane; 8 cathode; 9 anode; A is the oxygen-containing phase; B is the cathode reaction gas phase; C is the hydrogen-containing gas phase; D is the anode reaction gas phase. DETAILED DESCRIPTION
[0019] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0020] In the present disclosure, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of a device in normal use. Figure 1 In the drawing direction, "inside" and "outside" refer to the outline of the device. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present disclosure, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0021] like Figure 1 As shown, the first aspect of the present disclosure provides a proton exchange membrane fuel cell, the proton exchange membrane fuel cell comprises a bipolar plate and a membrane electrode assembly arranged in an internal chamber formed by the bipolar plate; the membrane electrode assembly comprises a proton exchange membrane, a catalyst layer and a diffusion layer sequentially arranged on both sides of the proton exchange membrane; the proton exchange membrane is doped with TiO 2 Nafion composite membrane; the catalytic layer includes a palladium-carbon catalyst and a Nafion membrane material; the average particle size of the palladium-carbon catalyst is less than 5 nm and the crystallinity is less than 4%; the diffusion layer is carbon black paper.
[0022] Through the above technical solution, doped TiO 2The Nafion composite membrane is used as a proton exchange membrane to form a dense titanium oxide network structure inside the Nafion membrane, which can improve the proton conductivity and chemical stability of the proton exchange membrane while improving the water absorption and water retention performance of the proton exchange membrane. The use of palladium-carbon catalysts and Nafion membrane materials with smaller average particle size and crystallinity can, on the one hand, improve the specific surface area and conductivity of the palladium-carbon catalyst, thereby improving the electrocatalytic performance of the catalyst layer; on the other hand, the Nafion membrane material can act as a binder, which can not only make the catalyst layer have stronger mechanical strength, but also improve the bonding ability between the catalyst layer and the proton exchange membrane, thereby improving the electrocatalytic stability. In addition, the proton exchange membrane fuel cell prepared using the membrane electrode assembly disclosed in the present invention has good electrochemical activity.
[0023] In a specific embodiment, the membrane electrode assembly 1 described in the present disclosure is composed of a proton exchange membrane 7, a cathode catalyst layer 6, an anode catalyst layer 5, a cathode diffusion layer 4, and an anode diffusion layer 3 from the inside to the outside. Among them, the cathode catalyst layer 6 and the cathode diffusion layer 4 are the cathode 8 of the proton membrane fuel cell, and the anode catalyst layer 5 and the anode diffusion layer 3 are the anode 9 of the proton membrane fuel cell.
[0024] In one embodiment, the bipolar plate 2 described in the present disclosure includes a cathode plate arranged on the outside of the cathode 8 and an anode plate arranged on the outside of the anode 9, wherein an anode flow field is formed between the anode plate and the anode 9 of the battery, and a cathode flow field is formed between the cathode plate and the cathode 8 of the battery.
[0025] In one embodiment, a fuel feed port and a combustion material outlet are provided on the anode plate, so that the hydrogen-containing gas phase C can enter the anode flow field through the fuel feed port and contact the battery anode for redox reaction, and the anode reaction gas phase D is obtained and exits the proton exchange membrane battery from the combustion material outlet. An oxygen-containing material inlet and an oxygen-containing material outlet are provided on the cathode plate, so that the oxygen-containing gas phase A can enter the cathode flow field through the oxygen-containing material inlet and contact the battery cathode for redox reaction, and the anode reaction gas phase B is obtained and exits the proton exchange membrane battery from the oxygen-containing material outlet. Among them, the fuel and the oxygen-containing material are conventionally selected in the art, and this application does not make special requirements. For example, the hydrogen-containing gas phase C is hydrogen, and the oxygen-containing gas phase A is air and / or oxygen.
[0026] In this embodiment, hydrogen loses two electrons under the action of the anode catalyst and is oxidized into hydrogen ions; the generated hydrogen ions pass through the proton exchange membrane to the cathode in a hydrated form, and the electrons reach the cathode after performing work on the load through the external circuit, thereby achieving conductivity and reducing to generate water. Air and / or oxygen are supplied through an air compressor, and under the action of the cathode catalyst, the oxidant combines with the hydrogen ions and electrons that reach the cathode to generate water, which is discharged with the exhaust gas. The overall reaction formula of the proton membrane fuel cell is: 2+2H 2 →2H 2 O, the theoretical voltage under standard conditions is 1.14V.
[0027] In one embodiment, the bipolar plate is made of stainless steel. In this embodiment, the stainless steel bipolar plate has good mechanical processing properties, which makes the flow field processing simple, and can be made into a bipolar plate with a thinner thickness. The quality and volume of the battery stack are significantly improved, the specific power is greatly improved, and the cost is greatly reduced, which meets the design goal of cheap and mobile requirements. However, it is easy to corrode in the high temperature and acidic environment where the battery works, which not only destroys the bipolar plate itself, but also the generated metal ions are absorbed by the proton exchange membrane, the proton conductivity of the membrane decreases, and after entering the catalyst layer, the catalyst activity will be reduced. Therefore, a conductive corrosion-resistant protective layer can be plated on its surface.
[0028] In one embodiment, a serpentine flow field groove is provided on the inner wall of the bipolar plate, and the ratio of the width of the serpentine flow field groove to the width of the ridge is (0.5~1):1. In this embodiment, the depth of the groove is determined by the total length of the groove and the total pressure drop of the reaction gas allowed to flow through the flow field. The serpentine flow field groove provided on the bipolar plate can make the gas phase flow of the cathode flow field and the anode flow field flow in a serpentine shape, and can make the gas phase flow fully contact with the entire cathode or anode, thereby improving the electrochemical performance of the battery.
[0029] In a preferred embodiment, the average particle size of the palladium carbon catalyst is less than 4 nm, and the crystallinity is less than 3%. In this embodiment, the palladium carbon catalyst used in the present disclosure is prepared by a solid phase reaction method. Since the probability of collision between particles in the solid phase system is low, the average particle size of the metal particles generated by the reaction is small and the crystallinity is low, so the electrocatalytic performance of the prepared catalyst is good.
[0030] In one embodiment, the content of the palladium-carbon catalyst in the catalyst layer and the thickness of the catalyst layer can be flexibly adjusted according to the setting parameters of the proton exchange membrane.
[0031] In the above embodiment, the use of a palladium-carbon catalyst with a small average particle size and crystallinity in the catalyst layer can increase the specific surface area and conductivity of the palladium-carbon catalyst, thereby improving the electrocatalytic performance of the catalyst layer. The Nafion membrane material used in the catalyst layer can act as a binder, which not only enables the catalyst layer to have a strong mechanical strength, but also improves the bonding ability between the catalyst layer and the proton exchange membrane, thereby improving the electrocatalytic stability. In addition, the thickness of the catalyst layer can be flexibly adjusted according to the setting parameters of the proton exchange membrane, which can improve the transfer effect of electrons and the effect of the membrane electrode assembly.
[0032] In one embodiment, the TiO in the Nafion composite membrane is flexibly adjusted according to the setting parameters of the proton exchange membrane.2 The content can form a denser titanium oxide network structure, which can further improve the proton conductivity and chemical stability of the proton exchange membrane, and the water absorption and water retention performance of the proton exchange membrane. In addition, the use of a proton exchange membrane of appropriate thickness can improve the electron transfer effect and the effect of the membrane electrode assembly.
[0033] In one embodiment, the diffusion layer is made of a mixture of carbon black or acetylene black and PTFE emulsion, and the diffusion layer has a uniform porous structure, good air permeability, low resistivity, strong electronic conductivity, compact structure, flat surface, reduced contact resistance, and improved electrical conductivity. In addition, the diffusion layer has a certain mechanical strength, appropriate rigidity and flexibility, which is conducive to the manufacture of electrodes and provides the stability of the electrode structure under long-term operating conditions; appropriate hydrophilic and hydrophobic balance to prevent excessive water from blocking pores and causing gas permeability to decrease; chemical stability and thermal stability; low manufacturing cost and high performance-price ratio. In addition, flexibly adjusting the thickness of the diffusion layer according to the setting parameters of the proton exchange membrane can improve the transfer effect of electrons and the effect of the membrane electrode assembly.
[0034] In one embodiment, the Nafion composite membrane and Nafion touch material described in the present disclosure are conventionally selected in the art, and this application does not make any special requirements.
[0035] The second aspect of the present disclosure provides a method for preparing the proton exchange membrane fuel cell described in the first aspect, the method comprising: arranging catalyst layers on both sides of the proton exchange membrane, and subjecting the catalyst layers to a first hot pressing process to obtain a first hot pressing component; arranging diffusion layers on the outer sides of the catalyst layers of the first hot pressing component, and subjecting the diffusion layers to a second hot pressing process to obtain a membrane electrode assembly; arranging the membrane electrode assembly in an internal chamber formed by a bipolar plate to obtain a proton exchange membrane fuel cell; the proton exchange membrane is doped with TiO 2 Nafion composite membrane; the catalytic layer includes a palladium-carbon catalyst and a Nafion membrane material; the average particle size of the palladium-carbon catalyst is less than 5 nm and the crystallinity is less than 4%; the diffusion layer is carbon black paper.
[0036] Through the above-mentioned implementation, the doped TiO 2 The Nafion composite membrane is used as the proton exchange membrane, the catalytic layer formed by the palladium-carbon catalyst with a small average particle size and crystallinity and the Nafion membrane material, and the carbon black paper is used as the membrane electrode assembly formed by diffusion and hot pressing. It has good electrochemical properties, strong mechanical strength and bonding strength, and electrocatalytic stability, thereby improving the electrochemical performance of the proton exchange membrane fuel cell.
[0037] In one embodiment, the method for preparing carbon black paper includes: mixing carbon black and a polymer binder evenly to obtain a carbon black slurry, then coating the carbon black slurry on the surface of carbon paper or carbon cloth, and finally performing a hot pressing treatment at a temperature of 330~370°C to obtain a diffusion layer.
[0038] In one embodiment, the carbon black is selected from acetylene black and / or VXC-72 carbon black.
[0039] In one embodiment, the polymer binder is a polytetrafluoroethylene (PTFE) emulsion.
[0040] In one embodiment, the carbon paper or carbon cloth is carbon paper or carbon cloth that has been subjected to hydrophobic treatment, wherein the hydrophobic treatment is a conventional choice in the art and is not specifically required in this application.
[0041] In one embodiment, the mass ratio of the polymer binder to carbon black is (0.25~1):1.
[0042] In one embodiment, the palladium-carbon catalyst is synthesized by a solid phase reaction method, and the specific method comprises: 2 PtCl 6 and NaOH solution, and vacuum-dry the obtained palladium-carbon slurry until the solvent is completely removed, and cool to 20-30° C. to obtain a palladium-carbon dry material; grind the palladium-carbon dry material and the solid phase reducing agent, filter, and wash with water until there is no Cl in the eluate. - Then, vacuum drying is performed at 90° C. to obtain the palladium-carbon catalyst; and the solid phase reducing agent is polyoxymethylene.
[0043] In one embodiment, the Pt content in the palladium-carbon catalyst is 15 to 30 wt %, preferably 15 to 25 wt %, and more preferably 20 wt %.
[0044] In one embodiment, the method further comprises mixing the palladium carbon catalyst, the Nafion solution and the mixed solvent to form a catalytic slurry, and drying the catalytic slurry at a temperature of 120-140° C. to obtain the catalytic layer.
[0045] In one embodiment, the concentration of the Nafion membrane material in the Nafion solution is 1 to 10 wt %, preferably 3 to 7 wt %.
[0046] In one embodiment, the mixed solvent is a mixed solution of glycerol and water.
[0047] In one embodiment, the weight ratio of the palladium carbon catalyst to the Nafion solution is (1-5):1, preferably (2-4):1.
[0048] In one embodiment, the weight ratio of the palladium-carbon catalyst, water and glycerol is 1:(1-10):(10-30), preferably 1:(3-7):(15-25).
[0049] In one embodiment, the method for preparing the proton exchange membrane comprises: subjecting the Nafion membrane to 2 O 2 The pretreated Nafion membrane is boiled in a solution and a sulfuric acid solution for 0.5 to 2 hours respectively, and then washed with water to obtain a pretreated Nafion membrane; the pretreated Nafion membrane is immersed in a mixed solution of isopropanol and water to obtain an expanded Nafion membrane; the expanded Nafion membrane is placed in a hydrolysis mixed solution for hydrolysis treatment, and the obtained hydrolyzed Nafion membrane is dried at a temperature of 75 to 85° C. for 18 to 30 hours to obtain the proton exchange membrane.
[0050] In one embodiment, the H 2 O 2 The mass fraction of the solution is 3-10%, preferably 4-6%.
[0051] In one embodiment, the concentration of the sulfuric acid solution is 0.3-1 mol / dm³, preferably 0.4-6 mol / dm³.
[0052] In one embodiment, the volume ratio of isopropanol to water in the mixed solution of isopropanol and water is 1:(2-10), preferably 1:(4-8).
[0053] In one embodiment, the performance of the composite film is similar to that of Ti(OC 4 H 9 ) 4 The hydrolysis mixed solution is Ti(OC 4 H 9 ) 4 and isopropanol mixed solution, the hydrolysis mixed solution of Ti(OC 4 H 9 ) 4 The concentration is 0.001~0.005mol / dm³; the temperature of the hydrolysis mixed solution is 60~90℃.
[0054] In a specific embodiment, the method for preparing the proton exchange membrane comprises: firstly, a Nafion membrane is placed in a 3-10% mass fraction of H 2 O 2 Solution, 0.3~1mol / dm³ H 2 SO 4The treated Nafion membrane was placed in a mixed solution of isopropanol and water with a volume ratio of 1: (2-10) and soaked at 20-30°C for 3 hours. The expanded Nafion membrane was then immersed in a Ti(OC 4 H 9 ) 4 The membrane was placed in an isopropanol solution for 3-4 hours. This process is the hydrolysis process. The membrane was taken out and washed with isopropanol and acetone respectively, and then rinsed with hot water at 80-85°C for 3 times. The membrane was then kept at 80°C for 24 hours.
[0055] In one embodiment, the method further includes uniformly coating the catalytic slurry on a polytetrafluoroethylene (PTFE) membrane, drying the catalytic slurry at a temperature of 120 to 140°C, and stacking the obtained first catalyst layer and second catalyst layer with the PTFE membrane on both sides of the proton exchange membrane, respectively, and performing hot pressing treatment so that the two catalytic layers are respectively attached to both sides of the proton exchange membrane, and then peeling off the PTFE membrane to obtain the first hot pressing component.
[0056] In one embodiment, the preparation Figure 1 The method of the proton exchange membrane fuel cell shown includes: Preparation of diffusion layer: acetylene black and / or VXC-72 carbon black and PTFE emulsion are uniformly mixed to obtain carbon black slurry, and then the carbon black slurry is coated on the surface of carbon paper or carbon cloth after hydrophobic treatment, and finally hot pressing is performed at a temperature of 330~370°C to obtain a diffusion layer; the mass ratio of the polymer binder to the carbon black is (0.25~1):1.
[0057] Preparation of proton exchange membrane: The method for preparing the proton exchange membrane comprises: firstly, placing a Nafion membrane in a 3-10% mass fraction of H 2 O 2 Solution, 0.3~1mol / dm³ H 2 SO 4 The treated Nafion membrane was immersed in a mixed solution of isopropanol and water with a volume ratio of 1: (2-10) for 3 hours (at 20-30°C). The expanded Nafion membrane was then immersed in a Ti(OC) solution at 70°C and a concentration of 0.001-0.005 mol / dm³. 4 H 9 ) 4 The membrane was placed in an isopropanol solution for 3-4 hours. This process is the hydrolysis process. The membrane was taken out and washed with isopropanol and acetone respectively, and then rinsed with hot water at 80-85°C for 3 times. The membrane was then kept at 80°C for 24 hours.
[0058] Preparation of palladium carbon catalyst: Make activated carbon, H 2 PtCl 6 and NaOH solution, and vacuum-dry the obtained palladium-carbon slurry until the solvent is completely removed, and cool to 20-30° C. to obtain a palladium-carbon dry material; grind the palladium-carbon dry material and polyoxymethylene, filter, and wash with water until there is no Cl in the eluate. - Then, vacuum drying is performed at 90° C. to obtain the palladium-carbon catalyst; the average particle size of the palladium-carbon catalyst is less than 5 nm, and the crystallinity is less than 4%.
[0059] Preparation of a proton exchange membrane fuel cell: the palladium carbon catalyst, Nafion solution and mixed solvent are mixed to form a catalytic slurry; the catalytic slurry is uniformly coated on a PTFE membrane, dried at a temperature of 120-140°C, and the first catalyst layer and the second catalyst layer with the PTFE membrane are respectively stacked on both sides of the proton exchange membrane, and hot-pressed so that the first catalyst layer and the second catalyst layer are respectively attached to both sides of the proton exchange membrane, and then the PTFE membrane is peeled off to obtain the first hot-pressed component. The diffusion layers are respectively arranged on the outer side of the catalyst layer of the first hot-pressed component, and the membrane electrode assembly is obtained by the second hot-pressing treatment. The concentration of the Nafion membrane material in the Nafion solution is 1-10% by weight; the mixed solvent is a mixed solution of glycerol and water; the weight ratio of the palladium carbon catalyst to the Nafion solution is (1-5):1; the weight ratio of the palladium carbon catalyst, water and glycerol is 1:(1-10):(10-30). The membrane electrode assembly is arranged inside the chamber formed by the bipolar plate to obtain a proton exchange membrane fuel cell.
[0060] A proton membrane fuel cell is prepared by the method described in the second aspect of the present disclosure.
[0061] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0062] Example 1 Preparation Figure 1 The method of the proton exchange membrane fuel cell shown includes: Preparation of diffusion layer: After acetylene black and PTFE emulsion are evenly mixed, carbon black slurry is obtained, and then the carbon black slurry is coated on the surface of carbon paper or carbon cloth after hydrophobic treatment, and finally hot pressing is performed at a temperature of 350°C to obtain a diffusion layer; the mass ratio of the polymer binder to carbon black is 0.5:1.
[0063] Preparation of proton exchange membrane: The method for preparing the proton exchange membrane comprises: firstly, placing a Nafion membrane in a 5% by mass H 2 O2 Solution, 0.5 mol / dm³ H 2 SO 4 The treated Nafion membrane was immersed in a mixture of isopropanol and water at a volume ratio of 1:3 for 3 hours (at 25°C). The expanded Nafion membrane was then immersed in a Ti(OC) solution at 70°C and a concentration of 0.0025 mol / dm³. 4 H 9 ) 4 The membrane was taken out and washed with isopropanol and acetone respectively, and then rinsed with 85°C hot water for 3 times, and then kept at 80°C for 24h.
[0064] Preparation of palladium carbon catalyst: XC-72R activated carbon powder, H 2 PtCl 6 and NaOH solution, and the obtained palladium carbon slurry is vacuum dried until the solvent is completely removed, and cooled to 25° C. to obtain a palladium carbon dry material; the palladium carbon dry material and polyoxymethylene are ground, filtered, and washed with water until there is no Cl in the eluate. - Then, vacuum drying was performed at 90° C. to obtain the palladium-carbon catalyst; the average particle size of the palladium-carbon catalyst was 3.8 nm and the crystallinity was 2.38%.
[0065] Preparation of proton exchange membrane fuel cell: the palladium carbon catalyst, Nafion solution and mixed solvent are mixed to form a catalytic slurry; the catalytic slurry is evenly coated on the PTFE membrane, dried at a temperature of 130°C, and the first catalyst layer and the second catalyst layer with the PTFE membrane are respectively stacked on both sides of the proton exchange membrane, and hot pressing is performed so that the first catalyst layer and the second catalyst layer are respectively attached to both sides of the proton exchange membrane, and then the PTFE membrane is peeled off to obtain the first hot pressing component. The diffusion layers are respectively arranged on the outer side of the catalyst layer of the first hot pressing component, and the membrane electrode assembly is obtained by the second hot pressing treatment. The concentration of Nafion membrane material in the Nafion solution is 5% by weight; the mixed solvent is a mixed solution of glycerol and water; the weight ratio of the palladium carbon catalyst to the Nafion solution is 3:1; the weight ratio of the palladium carbon catalyst, water and glycerol is 1:5:20. The membrane electrode assembly is arranged in the internal chamber formed by the bipolar plate to obtain a proton exchange membrane fuel cell.
[0066] The proton membrane fuel cell prepared by the present disclosure uses a Nafion composite membrane with a dense titanium oxide network structure formed inside as a proton exchange membrane, a palladium carbon catalyst and a Nafion membrane material with a small average particle size and crystallinity as a catalytic layer, and a carbon black paper formed by carbon black and a polymer binder as a diffusion layer. The proton exchange membrane fuel cell composed of the above components can not only improve the proton conductivity and chemical stability of the proton exchange membrane, but also obtain a proton exchange membrane fuel cell with good electrochemical activity.
[0067] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0068] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0069] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A proton exchange membrane fuel cell, characterized in that: The proton exchange membrane fuel cell includes a bipolar plate and a membrane electrode assembly disposed in an internal chamber formed by the bipolar plate; The membrane electrode assembly comprises a proton exchange membrane, a catalyst layer and a diffusion layer sequentially arranged on both sides of the proton exchange membrane; The proton exchange membrane is a Nafion composite membrane doped with TiO2; The catalytic layer includes a palladium-carbon catalyst and a Nafion membrane material; the average particle size of the palladium-carbon catalyst is less than 5 nm, and the crystallinity is less than 4%; The diffusion layer is carbon black paper.
2. The proton exchange membrane fuel cell according to claim 1, characterized in that: The average particle size of the palladium-carbon catalyst is less than 4 nm, and the crystallinity is less than 3%.
3. The proton exchange membrane fuel cell according to claim 1, characterized in that: The carbon black paper comprises carbon black and a polymer binder; The carbon black is acetylene black and / or VXC-72 carbon black; the polymer binder is polytetrafluoroethylene; The weight ratio of the polymer binder to the carbon black is (0.25-1):
1.
4. The proton exchange membrane fuel cell according to claim 1, characterized in that: The palladium content in the palladium carbon catalyst is 15-30% by weight.
5. The proton exchange membrane fuel cell according to claim 1, characterized in that: The material of the bipolar plate is stainless steel; A serpentine flow field groove is provided on the inner wall of the bipolar plate, and the ratio of the width of the serpentine flow field groove to the width of the ridge is (0.5~1):
1.
6. A method for preparing a proton exchange membrane fuel cell according to any one of claims 1 to 5, characterized in that: The method includes: The catalyst layers are respectively arranged on both sides of the proton exchange membrane, and subjected to a first hot pressing treatment to obtain a first hot pressing component; The diffusion layers are arranged on the outer sides of the catalyst layers of the first hot pressing parts respectively, and subjected to a second hot pressing process to obtain a membrane electrode assembly; The membrane electrode assembly is arranged in an internal chamber formed by a bipolar plate to obtain a proton exchange membrane fuel cell; The proton exchange membrane is a Nafion composite membrane doped with TiO2; The catalytic layer includes a palladium-carbon catalyst and a Nafion membrane material; the average particle size of the palladium-carbon catalyst is less than 5 nm, and the crystallinity is less than 4%; The diffusion layer is carbon black paper.
7. The method according to claim 6, characterized in that The method for preparing the palladium-carbon catalyst comprises: The palladium-carbon slurry obtained by mixing activated carbon, H2PtCl6 and NaOH solution is vacuum dried to obtain a palladium-carbon dry material; Grinding the palladium-carbon dry material and the solid-phase reducing agent to obtain the palladium-carbon catalyst; The solid phase reducing agent is polyoxymethylene.
8. The method according to claim 6, characterized in that The method further comprises mixing the palladium-carbon catalyst, the Nafion solution and the mixed solvent to form a catalytic slurry; Drying the catalytic slurry at a temperature of 120-140° C. to obtain the catalytic layer; The concentration of the Nafion membrane material in the Nafion solution is 1 to 10% by weight; The mixed solvent is a mixed solution of glycerol and water; The weight ratio of the palladium carbon catalyst to the Nafion solution is (1-5):1; The weight ratio of the palladium carbon catalyst, water and glycerol is 1: (1-10): (10-30).
9. The method according to claim 6, characterized in that The method for preparing the proton exchange membrane comprises: The Nafion membrane is boiled in H2O2 solution and sulfuric acid solution for 0.5 to 2 hours respectively and then washed with water to obtain a pretreated Nafion membrane; The pretreated Nafion membrane is placed in a mixed solution of isopropanol and water for immersion treatment to obtain an expanded Nafion membrane; The expanded Nafion membrane is placed in a hydrolysis mixed solution for hydrolysis treatment, and the obtained hydrolyzed Nafion membrane is dried at a temperature of 75-85° C. for 18-30 hours to obtain the proton exchange membrane.
10. The method according to claim 9, characterized in that The mass fraction of the H2O2 solution is 3-10%; the concentration of the sulfuric acid solution is 0.3-1 mol / dm³; The hydrolysis mixed solution is a mixed solution of Ti(OC4H9)4 and isopropanol, the concentration of Ti(OC4H9)4 in the hydrolysis mixed solution is 0.001-0.005 mol / dm³; the temperature of the hydrolysis mixed solution is 60-90°C.